Legal Substance of Sale and Purchase of Land and Building in the Determination of BPHTB DPP in Land and Building Sale and Purchase Transactions in Medan City - Siahaan, Albert Lodewyk Sentosa; Tonggo Michael Sihombing, Andy; Banke, Ricky (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
BPHTB is a levy on the acquisition of rights to land and buildings. In a transaction involving the buying and selling of property, the BPHTB tax is the responsibility of the buyer. This tax is charged on the acquisition of land and property rights and is calculated based on the Tax Object Acquisition Value stated in the sale and purchase agreement. Following the passage of Law Number 1 of 2022 regarding Financial Relationships between the Central and Local Governments, Law Number 28 of 2009 concerning these financial relations is rendered obsolete. The primary question this study addresses is: What is the legal substance of the BPHTB DPP relating to land and building transactions within the city of Medan? This investigation employs normative research approaches. The theoretical framework applied is Lawrence Friedman's theory of legal effectiveness. The DPP BPHTB for property sales and purchases is governed by the relevant regulations in Medan City, specifically the Medan City Regional Regulation Number 1 of 2024. The essence of the law must achieve the law's core objectives of Justice, Certainty, and Benefit. Ultimately, it can be concluded that the DPP BPHTB outlined in the Medan City Regional Regulation Number 1 of 2024 does not meet the legal goals envisioned by the law itself for the sale and purchase of land and buildings.